Revealing alterations in heart rate fluctuations during the progression of Chagas disease - Defeo, Magdalena M.; Delaplace, Laura A.; Goin, Juan C.; Tersigni, Carina; Garavaglia, Leopoldo; Irurzun, Isabel M. (Frontiers in Medicine, 2024)
The heart rate variability (HRV) continually evolves throughout life, reflecting modifications in the architecture of the sinoatrial node (SAN) and in the regulation of heart rate by the autonomic nervous system (ANS). Both can be considerably affected by Chagas disease, causing important changes in the complex nature of HRV. We aim to evaluate the ability of an index based on the false nearest neighbors method (FN10) to reflect these changes during disease progression. We determine the dependence of FN10 on age and sex in a healthy population, and then in individuals with Chagas disease. Finally, we relate the findings to the pathophysiological mechanisms that determine the progression of the disease.